UJI DAN SELEKSI ISOLAT KONSORSIUM MIKROB FILOSFER DAN RIZOSFER TERHADAP PERKECAMBAHAN BENIH PADI - Aris Aksarah Pas; Didy Sopandie; Trikoesoemaningtyas Trikoesoemaningtyas; Dwi Andreas Santosa (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
The application of microbes on the seeds of rice plants, microbes can enter into the rice seed tissues and growth in seed tissues, these microbes can colonize and survive and develop in the seeds. Colonization will continue when the plant grows. This study aims to select the phyllosphere and rhizosphere microbial consortium which can increase plant growth. Furthermore, choosing the best phyllosphere and rhizosphere microbial consortium to test its effectiveness in increasing rice growth. The test method was carried out by soaking the rice seeds (seed treatment) on each mixture suspension for 24 hours. Sprout power was observed after 2 days of incubation and root length, shoot length, wet weight and dry weight of seedlings were observed after 5 days. The method uses a Completely Randomized Design one treatment factor. The selection of the eight best consortium isolates was chosen based on the ranking after each parameter was given the weight multiplied by the scoring. The explored samples from various ecosystems in Sigi Regency contain the phyllosphere and rhizosphere microbial consortium. The isolates of the phyllosphere and rhizosphere microbial consortium have a positive, neutral and negative influence on rice seed germination. Can be selected for each of the eight best phyllosphere and rhizosphere microbial consortiums